1986
DOI: 10.1093/infdis/154.2.338
|View full text |Cite
|
Sign up to set email alerts
|

Production of Shiga-Like Toxin by Escherichia coli

Abstract: Production of Shiga-Like Toxin by Escherichia coli Escherichia coli is one of several agents that cause intestinal disease in humans and animals. Four classes of E. coli have been recognized [1], Enterotoxigenic E. coli (ETEC) strains produce a heat-labile (LT) enterotoxin and/or a heat-stable (ST) enterotoxin. Enteroinvasive E. coli (EIEC) strains, like shigellae, penetrate and multiply within epithelial cells. Enteropathogenic E. coli (EPEC) strains belong to certain serogroups that have been incriminated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 14 publications
5
88
0
1
Order By: Relevance
“…Microcytotoxicity assays were done on HeLa and Vero cells according to published modifications (27) of the methods of Gentry and Dalrymple (14). The last dilution of the sample in which greater than or equal to 50% of the HeLa or Vero cells detached from the plastic as assessed by A620 measurements was considered the 50% cytotoxic dose (CD50).…”
Section: Methodsmentioning
confidence: 99%
“…Microcytotoxicity assays were done on HeLa and Vero cells according to published modifications (27) of the methods of Gentry and Dalrymple (14). The last dilution of the sample in which greater than or equal to 50% of the HeLa or Vero cells detached from the plastic as assessed by A620 measurements was considered the 50% cytotoxic dose (CD50).…”
Section: Methodsmentioning
confidence: 99%
“…Another study revealed that 59% of strains from outbreaks of diarrhoea were SDT producers. Some strains of E. coli, however, that gave negative results when cell sonicates were used, gave positive results when French-press lysates were tested (Marques et al, 1986). Whether all EPEC strains produce SDT to some extent, and whether the inability to detect it results from a lack of sensitivity in the assay system, remains to be determined.…”
Section: Cytotoxinsmentioning
confidence: 99%
“…Diarrhoea caused by EAEC strains is generally less severe than that caused by EPEC strains. As some EPEC strains do not produce detectable Shiga toxin (Marques et al, 1986), they may in fact resemble EAEC strains. It should be noted, furthermore, that HEp2 adhesion in EAEC is distinct from that of EPEC strains (Levine, 1987).…”
Section: Adherence and Pathogenesismentioning
confidence: 99%
“…Therefore, we propose that independent translation of the slt-IL4 and slt-IIB genes is the sole factor governing the stoichiometry of SLT-II subunit production. Perhaps this explains why the level of SLT-II produced in vitro is significantly lower than that of STX (24).…”
Section: Discussionmentioning
confidence: 99%